Broadening the taxonomic scope of coral reef palaeoecological studies using ancient DNA. Issue 10 (14th May 2019) - del Carmen Gomez Cabrera, Maria; Young, Jennifer M.; Roff, George; Staples, Timothy; Ortiz, Juan Carlos; Pandolfi, John M.; Cooper, Alan
Abstract: Marine environments face acute pressures from human impacts, often resulting in substantial changes in community structure. On the inshore Great Barrier Reef (GBR), palaeoecological studies show the collapse of the previously dominant coral Acropora from the impacts of degraded water quality associated with European colonization. Even more dramatic impacts can result in the replacement of corals by fleshy macroalgae on modern reefs, but their past distribution is unknown because they leave no fossil record. Here, we apply DNA metabarcoding and high‐throughput sequencing of the 18S rDNA gene on palaeoenvironmental DNA (aeDNA) derived from sediment cores at two sites on Pandora Reef (GBR), to enhance palaeoecological studies by incorporating key soft‐bodied taxa, including macroalgae. We compared temporal trends in this aeDNA record with those of coral genera derived from macrofossils. Multivariate analysis of 12 eukaryotic groups from the aeDNA community showed wide variability over the past 750 years. The occurrence of brown macroalgae was negatively correlated only with the dominant coral at both sites. The occurrence of coralline and green macroalgae was positively correlated with only the dominant coral at one of the sites, where we also observed a significant association between the whole coral community and the occurrence of each of the three macroalgae groups. Our results demonstrate that reef sediments can provide a valuable archive for understanding the past distribution and occurrence of important soft‐bodied reef dwellers. Combining information from fossils and aeDNA provides an enhanced understanding of temporal changes of reefs ecosystems at decadal to millennial timescales. Abstract : see also the Perspective by Epp